Stage 1 Immature Ovarian Teratoma: Case Report - Correia, Paulo Manuel Costa; Coutinho Cabral, Liliana; Vale, Maria João; Santos, Maria Luís (Gazeta Médica, 2021)
Immature teratomas are rare malignant tumors, usually unilateral, solid, composed of undifferentiated tissues from the three embryonic germ layers: ectoderm, mesoderm and endoderm. Its classification is based on the quantity and degree of cellular immaturity of the neuroectodermal component (grades 1 to 3). The authors describe a clinical case of a 16-year-old woman with stage 1 immature ovarian teratoma with approximately 14 kg. Urgent salpingo-right ooforectomy was executed preserving the uterus and the left ovary and keeping the patient’s reproductive function. Subsequently, she was followed closely for 5 years in General Surgery outpatient consultations and had no evidence of cancer recurrence.